Structural insight on assembly-line catalysis in terpene biosynthesis - Jacque L. Faylo (Nature Portfolio, 2021)
Substrate channeling can improve biosynthetic efficiency and has been implicated in the reactions of fusicoccadiene synthase. Here, the authors analyze this bifunctional enzyme complex by cryoEM, cross-linking MS and integrative modeling, providing structural insights into how substrate channeling is achieved.